Destroying horseshoes via heterodimensional cycles: Generating bifurcations inside homoclinic classes - Díaz, L. J.; Horita, V. [UNESP]; Rios, I.; Sambarino, M. (Cambridge University Press (CUP), 2009)
In this paper, we propose a model for the destruction of three-dimensional horseshoes via heterodimensional cycles. This model yields some new dynamical features. Among other things, it provides examples of homoclinic classes properly contained in other classes and it is a model of a new sort of heteroclinic bifurcations we call generating. © 2008 Cambridge University Press.